Adult Stem Cells and Induced Pluripotent Stem Cells for Stroke Treatment - Fernández-Susavila, Héctor; Bugallo-Casal, Ana; Castillo, José; Campos, Francisco (Frontiers in Neurology, 2019)
Stroke is the main cause of disability and death in the world within neurological diseases. Despite such a huge impact, enzymatic, and mechanical recanalization are the only treatments available so far for ischemic stroke, but only <20% of patients can benefit from them. The use of stem cells as a possible cell therapy in stroke has been tested for years. The results obtained from these studies, although conflicting or controversial in some aspects, are promising. In the last few years, the recent development of the induced pluripotent stem cells has opened new possibilities to find new cell therapies against stroke. In this review, we will provide an overview of the state of the art of cell therapy in stroke. We will describe the current situation of the most employed stem cells and the use of induced pluripotent stem cells in stroke pathology. We will also present a summary of the different clinical trials that are being carried out or that already have results on the use of stem cells as a potential therapeutic intervention for stroke.